What Determines Where Public Investment Goes? Regional Governance and the Role of Institutional Rules and Power. (12th September 2020) - An, Brian Y.; Bostic, Raphael W.
Abstract: As an embodiment of the collaborative governance model, metropolitan planning organizations in the United States allocate federal, state, and local funds to member municipalities for transportation projects across their regions. To examine how institutional rules and power shape where public investment goes, the authors consider the extent to which the allocation of local voting power in regional governing policy boards influences the spatial allocation of transportation investments. The analysis shows that the power structure of regional policy boards is consistently a major factor associated with the observed geographic distribution of investments. Moreover, the results suggest that the degree of power concentration of the dominant city in the region influences whether the remaining cities' power matters. These results suggest that institutional governance rules may be more important than previously recognized.